2015
DOI: 10.4103/1817-1737.152450
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with poor asthma control in the outpatient clinic setting

Abstract: BACKGROUND/OBJECTIVES:The goal of the study was to assess asthma control using asthma control test (ACT) and to explore the factors that effects asthma control among participants with bronchial asthma in the outpatient clinic setting.METHODS:This cross-sectional descriptive study was conducted in the outpatient primary care clinic at King Abdulaziz Medical City in Riyadh. Adult patients who were diagnosed with bronchial asthma by their primary treating physician were recruited over a 6-month period. Patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…This also had a significantly increased impact on daily life and job choice. 35 Al-Zahrani et al 36 explored multiple factors that affect asthma control, including inappropriate device use by the patient, active smoking, passive smoking, an unsealed mattress, and workplace triggers. To our knowledge, this is the first study to explore relationships between the pathogeneses from working in a poor environment and asthma QoL.…”
Section: Discussionmentioning
confidence: 99%
“…This also had a significantly increased impact on daily life and job choice. 35 Al-Zahrani et al 36 explored multiple factors that affect asthma control, including inappropriate device use by the patient, active smoking, passive smoking, an unsealed mattress, and workplace triggers. To our knowledge, this is the first study to explore relationships between the pathogeneses from working in a poor environment and asthma QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a recent asthma control survey showed that only 5% of patients were controlled, 31% were partially controlled, and 64% were uncontrolled [16]. Al-Zahrani, et al [14] have been attributed this to certain risk factors, which included: inappropriate use of the inhaler device, active smoking, passive smoking, unsealed mattress, and workplace triggers were also associated with uncontrolled asthma.…”
Section: Introductionmentioning
confidence: 91%
“…Al-Zahrani et al [14]; Marchioro et al [15] contended that in accordance with the established international criteria, asthma is uncontrolled in the vast majority of asthma patients. Consistently, a recent asthma control survey showed that only 5% of patients were controlled, 31% were partially controlled, and 64% were uncontrolled [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous report has shown than the providers' factors, for example insufficient knowledge of current recommendations, resistance to changing practice, lack of time and resources also play an important role in the adherence to treatment. 21 The vital signs at presentation do not only indicate the severity and urgency of patients' condition, but also reflect the chance of developing status asthmaticus. 22,23 Our study showed that some initial vital signs (e.g.…”
Section: Discussionmentioning
confidence: 99%